2005
DOI: 10.1016/j.eurpsy.2005.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Hallucinogen persisting perception disorder after psilocybin consumption: a case study

Abstract: The recurrence of flashbacks without acute or chronic hallucinogen consumption has been recognized in the DSM IV criteria as the hallucinogen persisting perception disorder (HPPD). Perceptual disturbances may last for 5 years or more and represent a real psychosocial distress. We reported here a case of a 18-year-old young man presenting HPPD after a mixed intoxication with psylocibin and cannabis. This report shows symptomatic recurrences persisting more than 8 months. Various differential diagnoses were evok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 6 publications
0
34
0
4
Order By: Relevance
“…For example, Espiard et al (2005) reported HPPD in an 18-year-old man after mixed intoxication with psilocybin and cannabis. The symptoms persisted for more than 8 months.…”
Section: Hallucinogen Persisting Perception Disordermentioning
confidence: 99%
“…For example, Espiard et al (2005) reported HPPD in an 18-year-old man after mixed intoxication with psilocybin and cannabis. The symptoms persisted for more than 8 months.…”
Section: Hallucinogen Persisting Perception Disordermentioning
confidence: 99%
“…Table 7 summarizes cases of persistent psychiatric symptoms described in the literature. Espiard et al (2005) described a 18-year old student that appeared at the clinic with perceptual impairments. These were lasting for 8 months.…”
Section: Buck 1967mentioning
confidence: 99%
“…Just as with the rest of the simple tryptamines, psylocyne and psilocybine are considered substances with a wide margin of safety. Only one single decease has been reported up to date, and this was related with the massive consumption of Psilocybe semilanceata, as well as persistent perceptive disorder incidents due to hallucinogenic drugs (Espiard, Lecardeur, Abadie, Halbecq & Dollfus, 2005). Though both active principles are listed under category I of addictive substances, with no therapeutic potential acknowledged, anti-migraine or anti-obsessive properties have been reported.…”
Section: Hallucinogenic Mushrooms: Psilocybe Spmentioning
confidence: 99%